Improving Children’s Literacy Through Indonesian Fairy Tales at Rumah Pintar Yafsi - Pujiono, Mhd.; Nasution, Arie Azhari; Junaidi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Rumah Pintar YAFSI is one of the programs managed by Yayasan Fajar Sejahtera Indonesia to help develop character education and child protection programs in the community. Increasing literacy interest in children is an important aspect of character education that must be instilled. Improving children's literacy requires adequate facilities and education of high quality. As a result, in this service activity, the team has provided goods and services to the Rumah Pintar YAFSI, namely the assistance of Indonesian fairy tale books and storytelling training services for Rumah Pintar YAFSI volunteers to further strengthen children's interest in literacy. This is also an effort to achieve inclusive education for children of all socioeconomic backgrounds. The lecture method approach, question and answer or discussion, and deductive model training methods are used in the implementation. This community service improves Rumah Pintar YAFSI volunteers' storytelling skills, which in turn increases children's literacy interest in Rumah Pintar YAFSI. The outcomes of this activity have also been documented in written reports and videos. Furthermore, activities are reported in national online newspapers.